Introduction to Public Health: Course Material for HE100 - Kristi Murphey; Department of Health and Human Performance (2021)
This course is considered a public health “survey” class because it briefly introduces a wide variety of topics within the public health field. If you find you want more information on any of the topics, you will find links at the end of each section of this document that will direct you to more in-depth information. As a result of this class, you should be able to: Identify the multifaceted determinants of disease in population health. Identify the components of evidence based public health and apply them in a variety of public health situations. Identify the fundamental roles of public health and how those roles are exhibited in public health organizations, funding, workforce, and regulations. Identify and discuss the roles of public health in addressing health disparities and the needs of vulnerable populations. Identify one or more occupations within the public health realm and describe the education/ credentialing process to enter that field.